Colonial heritages, educational Incompartibilities and the challenges for a reunified Cameroon: 1961–2016 - Ndille, R. (My University, 2020)
The reunification of British Southern Cameroons and La Republique du Cameroun 1961 required the adoption of new national policies which were to guarantee that none of the colonial identities were jeopardized.1 In doing this, the Federal Republic adopted harmonization as a policy framework for the establishment of a new national educational system that was to unequivocally represent both colonial heritages without feelings of marginalization by any side. Using archival evidence and some empirical literature, this paper has examined the landmark developments in the harmonization of education in the country. It has observed that although significant strides have been made there are still huge challenges. The paper concludes that until both sides are determined to put national interests above former colonial interests, harmonization and the ultimate establishment of a national educational system cannot be achieved.2